Konsep Layanan Perpustakaan : Analisis Tafsir Surat Al-Maidah Ayat (2) - Ulfah Rulli Hastuti (THE LIGHT : Journal of Librarianship and Information Science, 2022)
The concept of library services has developed according to the needs of generations of users. The change is more to the design. Services in the form of guidance assistance to users in the process of searching for appropriate sources of information and referral sources, consulting assistance on the use of reference materials is a form of assistance to meet the needs of users. This research is a qualitative research with the type of library research. The data collection technique is literary, and the data analysis method is done by analyzing the content (content analysis). The results of the research through this analysis are that the concept of library services is in accordance with the interpretation of the letter Al-Maidah verse 2 that 1. there is assistance or assistance in the form of guidance to users in searching for appropriate reference or referral sources 2. providing training in tracing printed reference sources and digital (e- resources), guidance for users on how to be ethical in citing other people's work to avoid plagiarism violations. 3. an appeal to be more careful in identifying and using valid reference sources, maintaining and not damaging the collection. This is because the act is detrimental to others and is included in the act of tyranny. All forms of library services are conceptually a form of virtue (birru).